Adductor Canal Block Provides Noninferior Analgesia and Superior Quadriceps Strength Compared with Femoral Nerve Block in Anterior Cruciate Ligament Reconstruction. (May 2016) - Abdallah, Faraj W.; Whelan, Daniel B.; Chan, Vincent W.; Prasad, Govindarajulu A.; Endersby, Ryan V.; Theodoropolous, John; Oldfield, Stephanie; Oh, Justin; Brull, Richard
Abstract : Background: By targeting the distal branches of the femoral nerve in the mid-thigh, the adductor canal block (ACB) can preserve quadriceps muscle strength while providing analgesia similar to a conventional femoral nerve block (FNB) for inpatients undergoing major knee surgery. In this randomized, double-blind, noninferiority trial, the authors hypothesized that ACB provides postoperative analgesia that is at least as good as FNB while preserving quadriceps strength after outpatient anterior cruciate ligament reconstruction. Methods: A total of 100 patients were randomized to receive ACB or FNB with 20 ml ropivacaine 0.5% (with epinephrine). The authors sequentially tested the joint hypothesis that ACB is noninferior to FNB for cumulative oral morphine equivalent consumption and area under the curve for pain scores during the first 24 h postoperatively and also superior to FNB for postblock quadriceps maximal voluntary isometric contraction. Results: The authors analyzed 52 and 48 patients who received ACB and FNB, respectively. Compared with preset noninferiority margins, the ACB–FNB difference (95% CI) in morphine consumption and area under the curve for pain scores were −4.8 mg (−12.3 to 2.7) ( P = 0.03) and −71 mm h (−148 to 6) ( P < 0.00001), respectively, indicating noninferiority of ACB for both outcomes. The maximal voluntary isometric contraction for ACB and FNB at 45 min were 26.6 pound-force (24.7–28.6) and 10.6 pound-force (8.3–13.0) ( P < 0.00001), respectively, indicating superiority of ACB. Conclusion: Compared with FNB, the study findings suggest that ACB preserves quadriceps strength and provides noninferior postoperative analgesia for outpatients undergoing anterior cruciate ligament reconstruction. Abstract : In a randomized trial of 100 subjects undergoing anterior cruciate ligament, analgesia from adductor canal block was not inferior to that of femoral nerve block, but quadriceps muscle strength was superior.